Analysis of Urine Composition in Type II Diabetic Mice after Intervention Therapy Using Holothurian Polypeptides - Li, Yanyan; Xu, Jiajie; Su, Xiurong (Frontiers in Chemistry, 2017)
Hydrolysates and peptide fractions (PF) obtained from sea cucumber with commercial enzyme were studied on the hpyerglycemic and renal protective effects on db/db rats using urine metabolomics. Compared with the control group the polypeptides from the two species could significantly reduce the urine glucose and urea. We also tried to address the compositions of highly expressed urinary proteins using a proteomics approach. They were serum albumins, AMBP proteins, negative trypsin, elastase and urinary protein, GAPDH, a receptor of urokinase-type plasminogen activator (uPAR), and Ig kappa chain C region. We used the electronic nose to quickly detect changes in the volatile substances in mice urine after holothurian polypeptides fed, and the results show it can identify the difference between treatment groups with the control group without overlapping. The protein express mechanism of holothurian polypeptides treating diabetes was discussed, and we suggested these two peptides with the hypoglycemic and renal protective activity might be utilized as nutraceuticals.